The importance of STIs awareness in adolescence and how nursing can contribute to the reduction of these infections (Research, Society and Development, 2021)
This study has a qualitative approach and an explanatory-bibliographic character. It is based on Bonfim (2012), Nunes and Silva (2001), Valle and Mattos (2010), Benetti (1990), Costa e Silva (2019) Ministry of Health (2021) and among other authors who address the topic. The main objective sought to define the main causes and treatments of STIs in Brazil. It seeks to elucidate the following question: How can nursing contribute significantly to raising awareness of infections caused by STIs in adolescence? Initially, the concepts of AIDS in Brazil, STDs for STIs and Sexuality are presented. It is necessary to create the experience of an ethical, qualitative sexuality based on affective and bodily responsibility, especially in adolescence. Therefore, the specific objectives that enabled the results and understanding of this theme are: To carry out a brief history about the roots of adolescence and the beginning of AIDS in Brazil. Describe which are the most contagious frequent transmissible STIs for teenagers. Check how the health professional is essential for there to be adequate awareness among young people about their sexuality. Consider the possible forms of treatments for STIs and their application in today's daily life. Consider the role of the family in the search for the sexual understanding of young people. The research process, as well as the data collected, configure this scientific article based on a bibliographic survey, which provides information that aims to answer the general questioning of the study.